An investigation into school learners' perceptions of linguistic politeness norms within and across cultures - Kenyon, Tracy Karen (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2004)
The assumption underlying this study is that cultures differ in terms of politeness norms. Often people from different cultures approach one another in what they think is an appropriate manner and the outcome is miscommunication. This may be attributed to differing cultural norms and this study aims to examine what a sample of school learners perceive to be polite behaviour when making requests and their reasons for doing so. This study focuses on perceived politeness norms (Brown and Levinson 1978) in English across selected South African cultures. The individuals are seen as reflecting a cultural identity, using norms that they feel are appropriate in given situations. Previous researchers have endeavoured to show that politeness norms are universal, but it has emerged that this is not always the case. When people from differing language and cultural backgrounds come into contact they have to find a common ground for their interaction to be successful (Lustig and Koester 1999). Of particular interest is the way people request things, both the way they phrase their request and their reasons for phrasing it this way. In order to investigate this, twenty-nine same-sex pairs of Grade 10 learners were selected from three schools with different cultural backgrounds in Grahamstown. These learners were required to complete a Discourse Completion Test, which contained both Think-Aloud and Retrospection Procedures, while they were being audio-taped. This data was transcribed and analysed using a model that was developed and adapted to describe request strategies. This data is shown through the use of basic statistics, even though it is primarily qualitative. The data is given this qualitative dimension by looking at the factors that the co-conversants attend to. The recorded data shows that although second language speakers of English have a formula for requesting things, they are not always able to articulate why they use the request strategies they do. It appears that English first language speakers and speakers who have English as an additional language request things similarly, but the first language speakers have access to a greater variety of politeness strategies. They also attend to different contextual features. This shows that while the need to be polite seems to be universal, the expectations of the speakers will be different and while a first language speaker of English would not misinterpret the force of a given speech act, they may feel that the person who has English as an additional language is rude. Sensitivity is therefore called for in order to combat mutual negative stereotyping and misunderstandings.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Language policy -- South Africa; Multilingualism -- South Africa -- Eastern Cape; Language and education -- South Africa -- Eastern Cape; Language and culture -- South Africa -- Eastern Cape; Multiculturalism -- South Africa -- Eastern Cape; Social interaction -- South Africa -- Eastern Cape; Sociolinguistics -- South Africa -- Eastern Cape; Intercultural communication -- South Africa -- Eastern Cape; Speech acts (Linguistics)